An analysis of reading comprehension questions in promoting critical and creative thinking skills among year 6 students / Salamah Hj Mohamad - Mohamad, Salamah (2010)
It is crucial to educate our students in their aspects of critical and creative thinking skills (CCTS) so that they can learn to control and direct their own thinking and fully develop their potentials (Chua, 2004). Teaching reading comprehension is one of the ways to incorporate CCTS in the classroom. However, most of the students are unable to perform the more complex skills such as to give relevant and creative ideas, make inferences, make right decisions or solve problems. With this concern, this study is conducted to analyse the incorporation of CCTS in reading comprehension questions to Year 6 students in primary schools. The purpose of the study is to gather information regarding teachers' opinions of incorporating CCTS, their perception of students' level of thinking abilities and their implementation of CCTS in teaching reading comprehension lessons. The respondents were twelve teachers teaching the Year 6 classes from four selected schools in Shah Alam - Sekolah Kebangsaan TTDI Jaya, Sekolah Kebangsaan TUDM Subang, Sekolah Kebangsaan Seksyen 17 and Sekolah Kebangsaan Alam Megah 3. The instruments used in this study was a questionnaire to elicit information regarding the purpose of the study. Another instrumentation were 40 samples of reading comprehension exercises obtained from the schools which wereanalysed for the amount of CCTS elements. The major findings of this study were that teachers do incorporate CCTS in their teaching but are not sufficient to develop the students' critical and creative thinking skills. However some teachers were having problems to implement CCTS because they need more training to do so. Teachers also perceived that students are weak in their thinking abilities. Based on the analysis of the samples of reading comprehension questions, there was an average of 23.5% of CCTS questions only. This is considered insufficient to develop good thinking abilities. In conclusion, teachers have not given enough practice of CCTS through the teaching of reading comprehension and therefore should take further actions in order to implement the thinking skills more effectively. It is strongly recommended that teachers incorporate CCTS in the classroom so that the goals of the education system will be successfully achieved in developing well-rounded and balanced citizens. It is also recommended that further researches be carried out by involving more respondents and more samples so that more reliable findings can be obtained.